Faulkner, writer of disability - Hagood, Taylor, 1975- (Baton Rogue : Louisiana State University Press, 2014)
From the emerging field of disability studies, Taylor Hagood offers the first book-length consideration of impairment in William Faulkner's life and writing. Blending biography, textual analysis, and theory in an experimental style, Hagood explores in both form and content the constructs of normality and their power. Hagood brings to light little-known ways in which Faulkner's personal and familial background were marked by disability and discusses how the writer incorporates disability into his fiction. He reevaluates Faulkner's so-called "idiots"--Benjy Compson, Ike Snopes, and others - as characters whose narratives both satisfy and shock the reader. Hagood also examines the roles that impairment and abnormality play in the stories "The Leg" and "The Kingdom of God" and the novels A Fable and Flags in the Dust. Highly original readings result, including new understandings of the centrality of the visually impaired Pap in Sanctuary, the disability-centric social order based on interdependence in Pylon, and the disabled speech of Linda Snopes Kohl in The Mansion. Hagood argues that Faulkner's poetics are deeply invested in disability, both in promoting a disability-inclusive fictional world and in exposing and subverting the devaluation of disabled bodies and minds. Hagood draws on firsthand knowledge of his native Ripley, Mississippi, the ancestral home of the Faulkners, to offer readers otherwise inaccessible contextual information. Moreover, he employs a variety of genres - biography, digital communication, sensational horror, and filmic rhetoric - to probe Faulkner's own style and to question the standards of conventional scholarly criticism. This rich study offers insight into a Faulkner haunted by experiences of disablement and compelled to narrate them in his own writing. -- from dust jacket.
The Body of the Text -- A Note Pertaining to the Contents of the Body of the Text.
Includes bibliographical references (pages 199-208) and index.
Keywords: Faulkner, William, -- 1897-1962 -- Criticism and interpretation; Faulkner, William, -- 1897-1962.; Faulkner, William -- 1897-1962; People with disabilities in literature; People with disabilities in literature; Behinderung; Behinderter Mensch; Criticism, interpretation, etc